2014
DOI: 10.1289/ehp.1307359
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Effects of Tetrachloroethylene: Key Findings and Scientific Issues

Abstract: Background: The U.S. Environmental Protection Agency (EPA) completed a toxicological review of tetrachloroethylene (perchloroethylene, PCE) in February 2012 in support of the Integrated Risk Information System (IRIS).Objectives: We reviewed key findings and scientific issues regarding the human health effects of PCE described in the U.S. EPA’s Toxicological Review of Tetrachloroethylene (Perchloroethylene).Methods: The updated assessment of PCE synthesized and characterized a substantial database of epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(55 citation statements)
references
References 91 publications
(121 reference statements)
2
49
0
Order By: Relevance
“…However, a detailed examination of the effects of NAFLD on toxicokinetics of an environmental chemical and its metabolites in multiple tissues has not yet been reported. Because delivered dose of both PERC and its major metabolites may contribute to target organ-specific toxicity (Lash and Parker, 2001;Guyton et al, 2014;Cichocki et al, 2016b), such an examination is warranted for this ubiquitous environmental contaminant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a detailed examination of the effects of NAFLD on toxicokinetics of an environmental chemical and its metabolites in multiple tissues has not yet been reported. Because delivered dose of both PERC and its major metabolites may contribute to target organ-specific toxicity (Lash and Parker, 2001;Guyton et al, 2014;Cichocki et al, 2016b), such an examination is warranted for this ubiquitous environmental contaminant.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its widespread use, high production volume, and persistence in the environment, PERC has become a ubiquitous environmental contaminant of ambient air, soil, and drinking and ground water and is one of the most commonly found contaminants at hazardous waste sites (National Research Council, 2010). Exposure to PERC in humans and animals is associated with multiple target organ toxicity, including both cancer and noncancer toxicity (U.S. EPA, 2011;Guha et al, 2012;IARC, 2013;Guyton et al, 2014;Cichocki et al, 2016b). In mice, hepatotoxicity associated with PERC exposure is thought to be mediated by trichloroacetate (TCA), an oxidative metabolite of PERC (Bull et al, 1990;Bull, 2000;Corton, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of liver cancer was found in animal models exposed to PCE (CAS 127-18-4) [138,139] . Porru et al [140] showed that, in workers chronically exposed to organic solvents (toluene and xylene), there is an increased risk of HCC and that the risk is timedependent.…”
Section: -87-5mentioning
confidence: 99%
“…Table 3 summarizes the target organ carcinogenesis associated with TCE or PCE exposure. These data are derived from previous reports for TCE (Zhu et al, 2008;US EPA, 2011b;Chiu et al, 2013;IARC, 2014;National Toxicology Program, 2015) and PCE (US EPA, 2011a; IARC, 2014; Guyton et al, 2014).…”
Section: Metabolism and Metabolitesmentioning
confidence: 99%
“…There is some epidemiologic evidence for TCE-and PCE-associated noncancer hepatotoxicity (EPA, 2011a,b;Guyton et al, 2014). In most studies of TCE, liver dysfunction was monitored by serum liver enzyme levels and/or serum bile acid levels (Driscoll et al, 1992;Nagaya et al, 1993;Rasmussen et al, 1993b;Neghab et al, 1997;Davis et al, 2005;Kamijima et al, 2007;Xu et al, 2009).…”
Section: Noncancer Toxicitymentioning
confidence: 99%